Impact of preoperative use of P2Y12 receptor inhibitors on clinical outcomes in cardiac and non-cardiac surgery: A systematic review and meta-analysis. Issue 8 (1st December 2017) - Siller-Matula, Jolanta M; Petre, Alexandra; Delle-Karth, Georg; Huber, Kurt; Ay, Cihan; Lordkipanidzé, Marie; De Caterina, Raffaele; Kolh, Philippe; Mahla, Elisabeth; Gersh, Bernard J
Abstract: Objective: To review systematically the evidence and perform a meta-analysis of benefits and risks associated with use of P2Y12 receptor inhibitors in coronary artery bypass graft-, non-cardiac- and device surgery. Data selection and analysis: We performed a meta-analysis of published studies. Patients with preoperative use of clopidogrel, ticagrelor or prasugrel (late discontinuation: <5 days before surgery or no discontinuation) were compared with patients without preoperative use of the respective drug (early discontinuation: ⩾5 days before surgery or no users of P2Y12 receptor inhibitors). Outcomes evaluated were re-operation for major bleeding, death, myocardial infarction, combined major adverse cardiac events (MACEs) and major haematoma. Using a random effect model, relative risks (RRs) and 95% confidence intervals (CI) were calculated for each outcome. Results: Fifty-four studies met the selection criteria and included 50, 048 patients. Preoperative use of clopidogrel on top of aspirin in patients undergoing coronary artery bypass graft was associated with a 2.5-fold increased risk of re-operation for bleeding (95% CI: 1.92–3.25; p <0.001) and a 1.47-fold increased risk of death (95% CI: 1.25–1.72; p <0.001), but did not diminish the risk for myocardial infarction (RR: 0.96; 95% CI: 0.75–1.25; p =0.18) or MACE (RR: 1.16; 95% CI: 0.90-–1.50; p =0.30). In patients undergoing non-cardiac surgery, preoperative use of clopidogrel increased the RR of re-operation for major bleeding by 2.05-fold (95% CI: 1.13–3.73; p =0.002) but did not reduce the RR for MACE or death. Clopidogrel use during cardiac device implantation raised the RR for procedure-related haematoma by 3.0-fold (95% CI: 1.30-–6.94; p =0.001). Whereas preoperative ticagrelor use did not increase the risk for mortality (RR: 1.03; 95% CI: 0.49–2.14), preoperative prasugrel use tended to increase the risk for death (RR: 5.06; 95% CI: 0.54–47.65). Conclusion: Preoperative exposure to clopidogrel on top of aspirin did not reduce the risk of MACE but was associated with increased risk of bleeding and mortality.